THE PROTECTION OF ELDERLY PERSONS IN THE ACTIONS OF THE INTER-AMERICAN COMMISSION ON HUMAN RIGHTS - Miranda Bonilla, Haideer (2026)
The present study analyzes the degree of protection that the Inter-American Commission on Human Rights has recognized in the exercise of its main powers to older persons.